2013
DOI: 10.1155/2013/156798
|View full text |Cite
|
Sign up to set email alerts
|

Study of TNF-α, IL-1βand LPS Levels in the Gingival Crevicular Fluid of a Rat Model of Diabetes Mellitus and Periodontitis

Abstract: OBJECTIVE: In this study, we sought to investigate the dynamic changes in the levels of TNF-α, IL-1β and LPS in the gingival crevicular fluid (GCF) in a rat model of diabetes mellitus (DM) and periodontitis (PD). Additionally, we evaluated alveolar bone loss and the histopathological response associated with experimental diabetes mellitus and experimental periodontitis.METHODS: DM and PD were induced together in 15 rats (group 1) by streptozotocin injection and ligature induction. Periodontitis alone was produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 34 publications
5
59
0
1
Order By: Relevance
“…In addition to the leukocytes of the inflammatory infiltrate, the cells residing in the normal periodontium, including fibroblasts, junctional epithelial cells, and vascular endothelium (all of which function in the healthy periodontium to maintain homeostasis), can be hijacked by exposure to bacterial agents such as lipopolysaccharide (LPS), cytokines such as interleukin-1 (IL-1) or tumor necrosis factor- α (TNF- α ), or prostaglandins such as prostaglandin E2 (PGE-2) and become major participants in tissue destruction [8, 16, 17]. …”
Section: The Immune Response and Periodontal Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the leukocytes of the inflammatory infiltrate, the cells residing in the normal periodontium, including fibroblasts, junctional epithelial cells, and vascular endothelium (all of which function in the healthy periodontium to maintain homeostasis), can be hijacked by exposure to bacterial agents such as lipopolysaccharide (LPS), cytokines such as interleukin-1 (IL-1) or tumor necrosis factor- α (TNF- α ), or prostaglandins such as prostaglandin E2 (PGE-2) and become major participants in tissue destruction [8, 16, 17]. …”
Section: The Immune Response and Periodontal Diseasementioning
confidence: 99%
“…In patients with periodontal disease, IL-1 β expression was elevated in the GCF at sites of recent bone and attachment loss [17, 67, 68]. IL-1 β was also found to be higher in diseased periodontal tissue samples compared to tissue samples from healthy individuals, and the level of expression correlates highly with clinical parameters [64, 69].…”
Section: Inflammatory Cytokines and Periodontal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of such proinflammatory cytokines in the GCF has been associated with the production of reactive oxygen species (ROS) produced as a result of oxidative stress under periodontal inflammatory conditions 16 . In addition, an increased formation and accumulation of advanced glycation end products (AGEs) in the periodontal tissues under hyperglycemia has also been proposed to increase the burden of proinflammatory cytokines in the serum and GCF 17,18 . In this context, analysis of proinflammatory cytokines in GCF provides valuable information regarding the pathophysiologic processes associated with periodontitis.…”
mentioning
confidence: 99%
“…In a research C57BL Db/db mice that developed diabetes at six to eight weeks of age to study decreased osteoclastogenesis in bacteria-stimulated bone loss (He et al, 2004). Jiang et al (2013) reported resorption values of alveolar bone in the upper second molar of four groups of rats at different time points. The rats with periodontal disease (PD) and diabetes mellitus (DM) showed more alveolar bone loss than those with PD alone, DM alone, and control rats at the same time point.…”
Section: Bone Loss Is One Of the Complications In Diabetesmentioning
confidence: 99%